2019
DOI: 10.1371/journal.pone.0214248
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin and arterial stiffness in children with systemic lupus erythematosus and lupus nephritis: A cross-sectional study

Abstract: Background Cardiovascular disease is common in patients with systemic lupus erythematosis (SLE) and lupus nephritis (LN). Up to 80% of children with SLE develop kidney disease, which is also associated with increased risk for cardiovascular disease and death compared to those without renal involvement. Hepcidin is an iron-regulatory protein which may contribute to atherosclerosis and is elevated in autoimmune disease. Pulse wave velocity (PWV) is a validated indicator of arterial stiffness, an ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…This functional dysfunction was found active and in-remission SLE [ 8 ]. Atkinson et al found that PWV was elevated in a group of children with SLE with renal involvement [ 31 ], which may be associated with significant future exposure to CVD in these patients. Impaired renal function is associated with vascular calcification, even in the early stages of kidney disease, and may be associated with increased arterial stiffness [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This functional dysfunction was found active and in-remission SLE [ 8 ]. Atkinson et al found that PWV was elevated in a group of children with SLE with renal involvement [ 31 ], which may be associated with significant future exposure to CVD in these patients. Impaired renal function is associated with vascular calcification, even in the early stages of kidney disease, and may be associated with increased arterial stiffness [ 32 ].…”
Section: Discussionmentioning
confidence: 99%